Hydrated calcined Cyrtopleura costata seashells as an effective solid catalyst for microwave-assisted preparation of palm oil biodiesel. (1st June 2016) - Marwan,; Indarti, Eti
Highlights: Ca(OH)2 was derived from Cyrtopleura costata seashell by a relatively simple method. CaO of the calcined seashell reacted with atmospheric moisture for 7 days to form Ca(OH)2 . The highest biodiesel yield of 96% was obtained under microwave irradiation for 10 min. The hydrated-calcined seashell, Ca(OH)2 showed good activity in the transesterification. Abstract: The low-cost green catalyst, Ca(OH)2, derived from Cyrtopleura costata seashell was successfully prepared by a relatively simple method and examined for its performance in the transesterification of palm oil. Seashells containing 94% calcium were calcined at 900 °C for 2 h and hydrated by atmospheric moisture. XRD profiles revealed CaCO3 and Ca(OH)2 as the predominant compounds in the precalcined seashell sample and the resultant catalyst, respectively. In test runs, the transesterification of palm oil using hydrated calcined seashell was carried out in a batch reactor under microwave irradiation. The same reaction was also performed in a conventional reactor at higher temperature and pressure, but achieved a yield of only 59.2% after 2 h. The low reactivity of such solid catalysts was enhanced by the effects of microwaves at an intermolecular level. As a result, the reaction went to completion in a very short time at much milder conditions than in the conventional reactor. A maximum yield of 96.0% was attainable after a 10 min reaction with a catalyst loading of 0.5 g. Formation and quality of the fatty acid methyl ester product was confirmed by FTIR and GC analysis. The final biodiesel product met Indonesian, US, and European standards, except for viscosity, which was slightly above the European limit. Therefore, the hydrated calcined C. costata seashells effectively catalyze the microwave-assisted transesterification of palm oil to biodiesel.